Bone Marrow-Derived Stem Cell Transplantation for the Treatment of Insulin-Dependent Diabetes - Fotino, Carmen (SBDR - Society for Biomedical Diabetes Research, 2010)
The bone marrow is an invaluable source of adult pluripotent stem cells, as it gives rise to hematopoietic stem cells, endothelial progenitor cells, and mesenchymal cells, amongst others. The use of bone marrow-derived stem cell (BMC) transplantation (BMT) may be of assistance in achieving tissue repair and regeneration, as well as in modulating immune responses in the context of autoimmunity and transplantation. Ongoing clinical trials are evaluating the effects of BMC to preserve functional beta-cell mass in subjects with type 1 and type 2 diabetes, and to favor engraftment and survival of transplanted islets. Additional trials are evaluating the impact of BMT (i.e., mesenchymal stem cells) on the progression of diabetes complications. This article reviews the progress in the field of BMC for the treatment of subjects with insulin-dependent diabetes, and summarizes clinical data of pilot studies performed over the last two decades at our research center by combining allogeneic islet transplantation with donor-specific BMC.